2020
DOI: 10.1590/0074-02760200067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different total Leishmania amazonensis antigens for the development of a first-generation vaccine formulated with a Toll-like receptor-3 agonist to prevent cutaneous leishmaniasis

Abstract: BACKGROUND Unfortunately, no any vaccine against leishmaniasis has been developed for human use. Therefore, a vaccine based on total Leishmania antigens could be a good and economic approach; and there are different methodologies to obtain these antigens. However, it is unknown whether the method to obtain the antigens affects the integrity and immune response caused by them. OBJECTIVES to compare the protein profile and immune response generated by total L. amazonensis antigens (TLA) produced by different met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Recently, it was demonstrated that antigen similar to LaAg associated to poly I:C induced partial protection in BALB/c mice, and without adjuvant enhanced the lesion size and parasite load, as expected [46]. Poly I:C is a TLR3 ligand and a possible candidate in vaccine formulation against Leishmania spp.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, it was demonstrated that antigen similar to LaAg associated to poly I:C induced partial protection in BALB/c mice, and without adjuvant enhanced the lesion size and parasite load, as expected [46]. Poly I:C is a TLR3 ligand and a possible candidate in vaccine formulation against Leishmania spp.…”
Section: Discussionsupporting
confidence: 57%
“…The humoral immune response induced by the experimental treatment was evaluated by measuring total specific IgG, IgG1 and IgG2a by enzyme linked immunosorbent assay (ELISA) in serum samples collected on week 3 and 10 of the protocol. 11 …”
Section: Methodsmentioning
confidence: 99%
“…Twenty-one days after each immunization, blood samples were obtained from twice-immunized mice. Anti-TLA IgG antibodies were determined 21 days after prime and boost, while anti-TLA IgG1 and IgG2a isotypes were determined 21 days after boost by enzyme-linked immunosorbent assay ( 16 ). Thus, 96-well plates were incubated with 3 μg/well of TLA overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that Poly (I:C) can induce the cross-presentation of antigens by DC and, consequently, enhance the CD8+ T-cell response, which is important to control intracellular parasitic infection ( 15 ). Our research group has previously demonstrated that total L. amazonensis antigens (TLAs), obtained by cycles of freezing and thawing or sonication, combined with Poly (I:C) as adjuvant, were able to partially protect BALB/c mice against the L. amazonensis infection ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%